2011
DOI: 10.1016/j.jacc.2011.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Atherosclerosis Is Associated With Macrophage Polarization in Epicardial Adipose Tissue

Abstract: The ratio of M1/M2 macrophages in epicardial adipose tissue of CAD patients is changed compared with that in non-CAD patients. Human coronary atherosclerosis is associated with macrophage polarization in epicardial adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
276
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(300 citation statements)
references
References 28 publications
10
276
0
14
Order By: Relevance
“…This finding is justified according to the common embryogenesis pathway; that is, epicardial fat and intra-abdominal fat seem to be originally brown adipose tissue in infancy. This adipose depot is now recognized as a source of variable bioactive molecules, such as adiponectin (Iacobellis et al 2005b), tumor necrosis factoralfa, monocyte chemotactic factor-1, interleukine-1 beta, interleukine-6 (Mazurek et al 2003) and inflammatory cytokines which might affect coronary artery (Hirata et al 2011a(Hirata et al , 2011b. In fact, some epicardial fat-related cytokines, such as adiponectin, resistin, and free fatty acids, have been linked to hypertension, coronary artery disease, endothelial dysfunction, and sympathetic over activity (Bruun et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is justified according to the common embryogenesis pathway; that is, epicardial fat and intra-abdominal fat seem to be originally brown adipose tissue in infancy. This adipose depot is now recognized as a source of variable bioactive molecules, such as adiponectin (Iacobellis et al 2005b), tumor necrosis factoralfa, monocyte chemotactic factor-1, interleukine-1 beta, interleukine-6 (Mazurek et al 2003) and inflammatory cytokines which might affect coronary artery (Hirata et al 2011a(Hirata et al , 2011b. In fact, some epicardial fat-related cytokines, such as adiponectin, resistin, and free fatty acids, have been linked to hypertension, coronary artery disease, endothelial dysfunction, and sympathetic over activity (Bruun et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…25 Epicardial fat tissue is now recognized as a source of variable bioactive molecules 5,25 which might affect the coronary artery. 26,27 Our study results revealed that AS patients had increased EFT when compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 58%
“…8,50 In addition, epicardial fat obtained from patients with CAD has been shown to exhibit a pro-inflammatory polarization of M1/M2 macrophages. 51 A potential role of nuclear factor-κB and c-Jun N-terminal kinase pathways in the enhancement of inflammation observed in epicardial fat under CAD conditions has also been proposed. 2 In addition, higher oxidative stress levels, including reactive oxygen species production and higher levels of enzymes involved in regulating oxidative stress such as catalase and glutathione S-transferase P, have been reported in epicardial fat relative to subcutaneous fat in patients with CAD.…”
Section: Mechanisms Underlying the Pathophysiological Association Betmentioning
confidence: 99%